Ramucirumab plus triplet chemotherapy as an alternative salvage treatment for patients with metastatic colorectal cancer - Yi-Hsin Liang; Jin-Tung Liang; Ben-Ren Lin; John Huang; Ji-Shiang Hung; Shuo-Lun Lai; Tzu-Chun Chen; Jia-Huei Tsai; Yung-Ming Cheng; Ting-Han Tsao; Wen-Ling Hsu; Kuo-Hsing Chen; et al. (Journal of the Formosan Medical Association, 2022)
Background: Ramucirumab is indicated for salvage treatment after failure of first-line treatment for metastatic colorectal cancer (mCRC). However, the application of ramucirumab at later-line treatment in real-world practice has not received much discussion. Methods: In this retrospective study, we enrolled 70 patients with mCRC who received ramucirumab plus chemotherapy at National Taiwan University Hospital between 2018 and 2019. Results: Compared with those who received third- or later-line ramucirumab treatment, patients who received second-line ramucirumab treatment had significantly longer median time to treatment discontinuation (mTTD; 6.7 vs 3.6 months, P = .004) and median overall survival (mOS; not reached vs 7.6 months, P = .009). Multivariate analyses revealed that second-line ramucirumab and triplet chemotherapy backbone were the only independent predictive factors for long mTTD and mOS. Patients who received ramucirumab with triplet chemotherapy had a significantly longer mOS than did patients who received ramucirumab with doublet chemotherapy (not reached vs 5.6 months, P = .002). Among those receiving second-line ramucirumab treatment, combination with triplet chemotherapy led to a longer mTTD than did combination with doublet chemotherapy, but the difference was non-significant (not reached vs 4.4 months, P = .108). By contrast, in patients receiving fourth- or later-line ramucirumab, combination with triplet chemotherapy led to significantly longer mTTD than did combination with doublet chemotherapy (8.0 vs 2.9 months, P = .032). Conclusion: Ramucirumab plus triplet chemotherapy may be an alternative regimen in patients with mCRC, particularly as a later-line treatment modality.